PERTANGGUNGJAWABAN INTERNASIONAL NEGARA KETIGA DALAM KONFLIK BERSENJATA NON-INTERNASIONAL: ANALISIS DUGAAN DUKUNGAN UEA TERHADAP RAPID SUPPORT FORCE DI SUDAN: INTERNATIONAL RESPONSIBILITY OF THIRD STATES IN NON-INTERNATIONAL ARMED CONFLICTS: AN ANALYSIS OF ALLEGED UAE SUPPORT FOR THE RAPID SUPPORT FORCE IN SUDAN - Nugraha, Egi; Permanasari, Arlina (Fakultas Hukum Universitas Trisakti, 2025)
The non-international armed conflict (NIAC) between the Sudan Armed Forces (SAF) and the Rapid Support Forces (RSF) is currently one of the world’s largest humanitarian crisis. Allegations of support from the United Arab Emirates (UAE) to the RSF raise legal issues concerning the violation of the principle of third-state neutrality under international humanitarian law. This research applies the theories of international humanitarian law, neutrality, and state responsibility to analyze whether the alleged support provided by the UAE in Sudan’s internal conflict has breached international obligations and may influence the transformation of the conflict’s status into an international armed conflict (IAC). The findings show that the UAE’s involvement can be categorized as an internationally wrongful act, potentially triggering state responsibility. This study recommends strengthening international monitoring mechanisms to uphold and ensure the application of third-state neutrality in non-international armed conflicts.